Drinking, conduct disorder, and social change Navajo experiences - Kunitz, Stephen J.; Levy, Jerrold E., 1930- (New York ; Oxford : Oxford University Press, 2000)
Based on interviews with over 1000 Navajo Indian men and women, this monograph examines the associations between childhood experiences and behaviour and the development of alcohol dependence in adulthood.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Navajo Indians -- Alcohol use; Navajo Indians -- Social conditions; Alcoholism -- Psychological aspects; Antisocial personality disorders